Metaphors of the sea : a critical study of five Anglo-Saxon poems - Green, Brian Keith (Department of English Language and Literature, 2016)
The object of this thesis is to contribute to the appreciation of five selected Anglo-Saxon poems - The Wanderer, The Seafarer, Exodus, Andreas, and Beowulf - by analysing their metaphoric use of the sea. Metaphor is an essential and distinctive element of all poetry and, to be genuine, to be alive, and to be ever-interesting, a poem must achieve itself through metaphor. A poem's unique mode of vision is metaphoric, and whatever it communicates we perceive in and through metaphor. This is an axiomatic tenet of the criticism of modern poetry. But criticism of Anglo-Saxon poetry, if it bases its insights on a detailed reference to metaphor, must justify itself on theoretical grounds.